TAHAPAN PENGEMBANGAN E-GOVERMENT DALAM PENDIDIKAN - Fenny Purwani (Wardah, 2014)
E-Governance is composed of two important things that 'governance' as the main concepts and 'electronic'atau ICTs (Information and Communication Technologies) as a tool to improve the process of governance. E-Government can be applied to the legislative, judicial, or public administration, to improve internal efficiency, deliver public services, or processes of democratic governance. E-Government can be applied in all areas, including in education. The role of information and communication technology in education is also very large, especially in terms of supporting the teaching-learning process and the efficiency of academic and administrative jobs. College as one of the educational institutions are appropriately able to utilize information and communication technologies to support various activities of e-govement. Because it also needs to be adapted in the world of education.